Pertanian Organik Sebagai Upaya Peningkatan Perekonomian Masyarakat di Lembang Basokan - Stefani Marina Palimbong; Olivia Devi Yulian Pompeng; Astriwati Biringkanae; Lisa Kurniasari Wibisono; Elisabet Pali; Yohanis Lotong Ta’dung (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
Organic farming is a farming system that emphasizes the use of natural ingredients without the use of synthetic chemicals, making it more environmentally friendly and sustainable. The implementation of organic farming not only aims to preserve the environment but also has the potential to increase productivity and community economic well-being. This training and outreach activity was held in Lembang Basokan, Nanggala District, North Toraja Regency, with the aim of increasing community understanding and skills regarding organic farming methods. The main focus of this activity was the use of natural liquid organic fertilizer, which is easy to make, environmentally friendly, and has greater benefits for plant growth and health. The implementation method included counseling, demonstrations of liquid organic fertilizer production, and interactive discussions with the community. The outreach strategy was designed in a communicative and participatory manner to attract community interest and encourage active participation throughout the activity. The results of this activity indicate an increased community understanding of the concept of organic farming and the benefits of using liquid organic fertilizer. Furthermore, the community also expressed interest in implementing organic farming practices as an alternative to increase agricultural yields and improve the family economy. Therefore, this organic farming training and outreach activity is expected to be the first step in developing sustainable agriculture in Lembang Basokan.